1997
DOI: 10.1038/sj.onc.1201429
|View full text |Cite
|
Sign up to set email alerts
|

Insulin activates Stat3 independently of p21ras-ERK and PI-3K signal transduction

Abstract: The binding of insulin to its receptor initiates multiple signal transduction pathways regulating such diverse processes as proliferation, di erentiation, glucose transport, and glycogen metabolism. The STAT-family of transcription factors has been demonstrated to play a critical role in gene induction by a variety of hemopoietic cytokines and hormones. Furthermore, constitutive activation of STATs is observed in transformed cells. Here we describe activation of a transcriptional complex binding to a consensus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
80
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 49 publications
3
80
0
1
Order By: Relevance
“…UV light induces ligand-independent activation of various receptors, receptor tyrosine kinases, and protein tyrosine kinases at the inner side of the plasma membrane (36)(37)(38)(39)(40). Recently, UV light was found to cause epidermal and plateletderived growth factor receptor autophosphorylation by inhibiting dephosphorylation of these receptors, presumably by targeting membrane-associated protein tyrosine phosphatases (41).…”
Section: Discussionmentioning
confidence: 99%
“…UV light induces ligand-independent activation of various receptors, receptor tyrosine kinases, and protein tyrosine kinases at the inner side of the plasma membrane (36)(37)(38)(39)(40). Recently, UV light was found to cause epidermal and plateletderived growth factor receptor autophosphorylation by inhibiting dephosphorylation of these receptors, presumably by targeting membrane-associated protein tyrosine phosphatases (41).…”
Section: Discussionmentioning
confidence: 99%
“…Ligand-independent phosphorylation of receptor tyrosine kinases, induced by UV irradiation, is known to represent a rapid, membrane-associated event (Sachsenmaier et al, 1994;Coffer et al, 1995;Huang et al, 1996;Rosette and Karin, 1996). Here we show that also the receptor for KGF, which plays a fundamental role in regulating keratinocyte growth and differentiation, is rapidly phosphorylated by exposure to physiological doses of UVB with timing and efficiency similar to that induced by binding of the ligand to the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…The earliest step in response to UV irradiation and subsequent ROS generation involves ligand-independent phosphorylation of growth factor receptors such as epidermal growth factor receptor (EGFR) (Sachsenmaier et al, 1994;Coffer et al, 1995;Huang et al, 1996;Peus et al, 1998Peus et al, , 1999, signal transduction (Sachsenmaier et al, 1994;Rosette and Karin, 1996) and rapid expression of early growth response genes (Egr-1) (Huang and Adamson, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown that STAT3 could be phosphorylated by insulin in vitro (14,15). However, the biological effect of the activation remains unknown, probably due to the lack of an animal model resulting from embryonic lethality in generalized STAT3 ablation.…”
mentioning
confidence: 99%